Comparing two antiseptic solutions for scrubbing - Yuldashkhan, M; Bolurchifard, F; Amiri, Z (Advances in Nursing & Midwifery, 2008)
Introduction Scrubbing of surgical team is an important precaution for postoperative infections. It is performed to disinfect the hands, leading to secondary infection reduction of surgical wound. The procedure is done mechanically and chemically with scrub solutions such as povidone iodine, alcoholic disinfectants, chlorhexidine etc. In Iran, the routine solution of scrubbing is povidone iodine (Betadine). The Purpose of this clinical trial was to compare the disinfectant effects of Betadine with Decosept on the hands of surgical team in Loghman-e-Hakim teaching hospital affiliated to Shaheed Beheshti Medical University. Materials and Methods 30 operating room (OR) staff and students were selected by convenient sampling method. Each subject scrubbed 2 times with 1-week interval, first with Betadine and second with Decosept. All members of a surgical team in an operation scrubbed with a similar method and solution. Samples were collected from the hands before and after scrubbing for the first scheduled operation through instructing the procedure (hand washing with soap and water, rinsing, complete drying, application 15 ml of one of the solutions in three stages [at each stage, 5 ml and 1-minute interval], rinsing and complete drying), placing the hands in culture media and sending the samples to laboratory in standard condition for recording. Results Findings showed significant differences in the colonies of Gram-positive cocci, Gram-negative bacilli and fungi before and after scrubbing in each solution (P=0.0001). No positive case was found before and after the procedure with respect to Gram-negative cocci and Gram-positive bacilli. No significant difference was found between the effects of the 2 solutions before and after scrubbing. Conclusion Both solutions were effective on disinfecting the hands of surgical team. Keywords: Povidene (Betadine), Decosept, Scrubbing, Disinfection.